Intellectual property rights (IPR) issues in livestock biodiversity -Indian perspective - KP Ramesha; R Pourouchottamane; MA Kataktalware; M Sarkar (Journal of Livestock Biodiversity, 2025)
Commercial interests in the new developments in biotechnology led to pressure being exerted onWorld Trade Organization (WTO) member states to provide better patent protection in livestock agriculture.Harmonization of national laws, particularly dealing with intellectual property rights in different areas includinganimal agriculture is one of the major impacts of GATT/WTO. Convention on Biological Diversity (CBD)recognizes the sovereign rights of nations over their genetic resources, including the capacity to establishconditions of access and fair and equitable sharing of benefit from the use of such resources. In spite of greateconomic and biological importance, even today a legal framework for animal genetic resources comparableto International Treaty on Plant Genetic Resources doesn't exist. Such a legal framework should contribute toglobal food security, and also benefit biodiversity rich under developed and developing countries".